A comparative study oıı the histomorphology of olfactory bulb in greyhound and outdoor dog - Mehmet Kanter (Eurasian Journal of Veterinary Sciences)
In the present study, ollactory bulbs of greyhound and outdoor dogs were compared histologically. It was found that the olfactory bulbs of both species were constituted by accessory and main parts having the same layers (nerve, glomerular, eksternal pleksitorm, mitral cell, internal pleksiform and granular cell). Nerve, glomerular and mitral cell layers were very wide and there were many glial cells in the last two layers in the olfactory bulbs of greyhound. However, tn outdoor dog. these layers were very narrow and there were few mitral and glial cells. Differences in the smelling ability between greyhounds and outdoor dogs were thought lo be depended on the histomorphological differences ot their olfactory bulbs.